Identification and Characterization of Soft Rot Bacterial Pathogens on Phalaenopsis Orchid in Bali - I Putu Wirya Suputra; Gusti Ngurah Alit Susanta Wirya; Nyoman Bintang Kartika Sari; I Gede Rai Maya Temaja; Ni Luh Putu Citra Innosensia (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2022)
The moth orchid (Phalaenopsis sp.) is one of the most popular orchids due to the various colors with distinctive shapes of the flowers. Soft rot disease caused by Pectobacteriaceae (SRP) family is commonly found infected this plant. The infected orchid showed pale-colored to blackish slimy rot. This research was conducted in three locations namely Denpasar, Badung, and Karangasem, and resulted in 10 candidates for pathogenic bacteria. The pathogenicity test of the pathogen candidates was carried out by injecting bacterial suspension into the orchid leaf tissue with the result of 6 bacterial isolates showing soft rot symptoms. Moreover, two specific primers Dda1F-Dda1R and Pcc3F-Pcc3R for Dickeya spp. and Pectobacterium spp. consecutively were used for the PCR test. The electrophoresis result of the PCR product identified the bacteria isolated from infected plants as Dickeya spp. Dickeya spp. showed white to yellowish-white colony color, with convex and circular colony form on PDA medium.